Sistem Informasi Pengolahan Data Nilai Raport Terintegrasi di PAUD - Rachman, Andi Nur; Gufroni, Acep Irham; Sulastri , Heni; Dewi , Euis Nur Fitriani (Universitas Islam Indonesia, 2025)
Developments in technology and science have had a big effect on life, including in the field of education. Many schools from high school, middle school, elementary school, even kindergarten or PAUD are developing themselves to provide quality learning or educational services by implementing computer-based information systems. The current problem is that the recording of report card scores as a child's development is done manually or written in a report card, this makes it difficult to find out the child's development graph. So there is a need for a system that helps facilitate the assessment of report cards and progress charts preschool children's education. The method used in this service is a descriptive research design method. Service activities in the system development process that will be proposed are the waterfall method. An integrated report card data processing information system to make things easier for PAUD schools. The information system makes things easier for students or parents in checking report scores via the website..